Synthesis and characterization new Polymerizable Liquid Crystal Monomer and its atom transfer Radical Polymerization for novel side chain Liquid Crystalline Polymers - Sheikh, M.R.K.; Masuyama, S.; Tokita, M.; Watanabe, J. (2009)
We synthesized a new polymerizable liquid crystal (LC) monomer, which contain naphthalene ring in the mesogen. The new LC monomer was characterized by IH NMR, Polarized Optical Microscope (POM), Differential Scanning Calorimeter (DSC) and Wide Angle X-ray Diffractometer (WAXD) measurements. Living Atom Transfer Radical Polymerization (ATPR) was used to synthesize side chain liquid crystalline p,0lymers (SCLCPs) of different molecular weight. The SCLCPs were characterized by H NMR, Gel Permeation Chromatogram (GPC), POM, DSC and WAXD. The SCLCPs showed isotropization at 179°C, a very wide range nematic phage appeared from 177-117 0C temperature region and smetic A phage appeared at or below 117°C. The glass transition temperature (Tg) was increased with the increase of molecular weight (Mn) of SCLCPs.